Capital and ecology : developmentalism, subjectivity and the alternative life-worlds - Bhattacharya, Rakhee; Sharma, G. Amarjit (Oxon : Routledge, 2024)
"This volume studies the intersection of capital and ecology primarily in one of the most sensitive geographies of the world, the Eastern Himalayan region. It looks at how the region has become a melting ground of neoliberal developmentalism and ecological subjectivities with the penetrating forces of global and state capitalism, economic projects, and complex power relations. The essays in the volume argue that specific focus on energy infrastructure and energy production has pushed technology and capital towards asset building which has had an adverse effect on the environment, labour relations, indigenous knowledge systems, and traditional livelihood practices in the area. They look at assets like mega dams, electricity transmission networks, natural gas grids, infrastructural and developmental projects, and other alternative ventures which require interventions in the natural world and its resource deposits."--
Keywords: Energy Industries; Sustainable development